Fayzulla Khodjayev - National and Political Leader of the Uzbek People - Rafikov Kudratilla Mirsagatovich (Indonesian Journal of Public Policy Review, 2022)
This article analyzes the activity of Fayzulla Khodjaev, the leader of the "Young Bukhara" party, the chairman of the government of the Soviet Socialist Republic of Uzbekistan in 1924-1937, the political leader of the Uzbek nation, as a political and state chairman. Despite the fact that Fayzulla Khodjaev was a communist, the All Union of Russia at that time was critical of the methods and ideology of the Russian Communist Party. He contributed a lot to the development of industry, agriculture and culture of Uzbekistan in 1924-1937. During his tenure as the head of the government, the rate of development of the state and society of Uzbekistan accelerated. Dictator Joseph Stalin did not like the fact that Fayzulla Khodjaev enjoyed great prestige among the people and had the qualities of a political leader back in the days of the former USSR. Moscow did not particularly like the courage, truthfulness of Fayzulla Khodjaev and the fact that he followed the people. Stalin also suspected that he might try to separate Uzbekistan as an independent state. Fayzulla Khodjaev was shot in 1937 by order of Stalin. The article mainly analyzes the political events and processes of the 20-30s of the twentieth century, reveals the original image and ideology of the Bolshevik Party.